Production of PHB From CO2-Derived Acetate With Minimal Processing Assessed for Space Biomanufacturing - Cestellos-Blanco, Stefano; Friedline, Skyler; Sander, Kyle B.; Abel, Anthony J.; Kim, Ji Min; Clark, Douglas S.; Arkin, Adam P.; Yang, Peidong (Frontiers in Microbiology, 2021)
Providing life-support materials to crewed space exploration missions is pivotal for mission success. However, as missions become more distant and extensive, obtaining these materials from in situ resource utilization is paramount. The combination of microorganisms with electrochemical technologies offers a platform for the production of critical chemicals and materials from CO2 and H2O, two compounds accessible on a target destination like Mars. One such potential commodity is poly(3-hydroxybutyrate) (PHB), a common biopolyester targeted for additive manufacturing of durable goods. Here, we present an integrated two-module process for the produc-tion of PHB from CO2. An autotrophic Sporomusa ovata (S. ovata) process converts CO2 to ace-tate which is then directly used as the primary carbon source for aerobic PHB production by Cupriavidus basilensis (C. basilensis). The S. ovata uses H2 as a reducing equivalent to be generated through electrocatalytic solar-driven H2O reduction. Conserving and recycling media components is critical, therefore we have designed and optimized our process to require no purification or filtering of the cell culture media between microbial production steps which could result in up to 98% weight savings. By inspecting cell population dynamics during culturing we deter-mined that C. basilensis suitably proliferates in the presence of inactive S. ovata. During the bio-process 10.4 mmol acetate L-1 day-1 were generated from CO2 by S. ovata in the optimized media. Subsequently, 12.54 mg PHB L-1 hour-1 were produced by C. basilensis in the unprocessed media with an overall carbon yield of 11.06% from acetate. In order to illustrate a pathway to increase overall productivity and enable scaling of our bench-top process, we developed a model indicating key process parameters to optimize.